Model Konseptual Struktur Cerita Untuk Pengembangan Game: Studi Kasus Program Microcredential Game Developer - Roedavan, Rickman; Ramdhan, Dimas; Purwanto, Agus (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2024)
Storytelling is the most crucial component in games as it provides emotional stimulation, thereby enhancing player interest and immersion. However, commonly used storytelling models like the Three Act Structure, Freytag's Pyramid, and Hero's Journey are linear and not specifically mapped for game development. This study aims to develop a conceptual model of digital storytelling structure specifically for game development. The research methods include the analysis of existing storytelling models, the development of a new framework, and testing on 54 student teams from 166 universities, institutes, and polytechnics in Indonesia participating in the Microcredential Game Developer Program (PMGD). The testing results show that the conceptual storytelling structure model can provide story variation in game development. Additionally, this model allows for easier and more structured integration with game mechanics development. This model is expected to provide a foundation for further research to optimize storytelling techniques in games.